FACTORS INFLUENCING INVESTMENT DECISION MAKING IN SWIFTLET RANCHING INDUSTRY: THE CASE OF GUA MUSANG AND JOHOR BAHRU - Fatin F. Ya’acob; Mohd Shahwahid Haji Othman; Rabiatul Munirah Alpandi; Siti Mariam Mellisa Abdulla; Mohd Hafiz Ghazali (JOURNAL OF TOURISM, HOSPITALITY AND ENVIRONMENT MANAGEMENT (JTHEM), 2024)
Edible bird nest industry is an entry point project under the Malaysian Transformation Plan. The number of swiftlet houses has increased three and a half folds from 2011 to 2016 but with this trend swiftlet houses, failure ranged from 70 to 80 percent. This study focuses on understanding the investors’ behavior in this industry and on determining factors that are influencing their investment decision. The basic framework of analysis is the investor behavior theory by applying for the formative first order Partial Least Squares-Structural Equation Modelling model. The data collected from 180 ranchers randomly interviewed from two districts namely Johor Bahru and Gua Musang. The result revealed that heuristic is a first decision construct that has the highest impact on investment decision making followed by market, herding and prospect decision construct.